Clinical determinants of a positive visual inspection after treatment with acetic acid for cervical cancer screening. (28th February 2014) - Castle, PE; Qiao, Y‐L; Zhao, F‐H; Chen, W; Valdez, M; Zhang, X; Kang, L‐N; Bansil, P; Paul, P; Bai, P; Peck, R; Li, J; et al.
<x xml:space="preserve">Abstract</x> Objective To examine the determinants of a positive visual inspection after acetic acid (VIA), including the relationship of testing positive for high‐risk human papillomavirus (HR‐HPV), which is the necessary cause of cervical cancer. Design A prospective cohort study. Setting Three clinical sites in rural China. Population A total of 7541 women aged 25–65 years. Methods All women underwent VIA, DNA testing, by two DNA tests performed on both clinician‐ and self‐collected specimens, and HPV E6 oncoprotein testing. Those positive by any test underwent colposcopy and four‐quadrant biopsy evaluation. A random sample of women with negative screening results also underwent colposcopy and, if colposcopic abnormalities were observed, four‐quadrant biopsy evaluation was performed. Women diagnosed with cervical intraepithelial neoplasia grade 2 (CIN2), or more severe grades (CIN2 + ), underwent treatment. Main outcome measure Testing positive for VIA. Results Overall, 7.6% (95% confidence interval, 95% CI, 7.0–8.2%) had a positive VIA. Women who tested positive for HPV were more likely to have a positive VIA than women who tested negative for HPV (15.0%, 95% CI 12.9–17.2% versus 6.3%, 95% CI 5.7–6.9%; P < 0.001). Older women were less likely to have a positive VIA (Ptrend < 0.001), including women with CIN2 + (Ptrend < 0.001). A logistic regression model demonstrated that diagnosis (CIN2 + versus <CIN2; odds ratio, OR, 32; 95% CI 11–100), testing HPV positive with a higher viral load (highest versus lowest; OR 4.3; 95% CI 2.5–7.4), and age (51 years and older versus <38 years; OR 0.22; 95% CI 0.17–0.30) were independent determinants of having a positive VIA. VIA was more likely to be positive for women with CIN2 + having an abnormal colposcopic impression versus women with CIN2 + regardless of colposcopic impression (71.4 versus 47.2%). Conclusions The age of the population and method of disease ascertainment should be considered in the interpretation of any VIA performance.